153k views
1 vote
Imagine that the following "solution" was (x²+10x+9)/(x+9)=(x²+10x)/(x)=x+10

Is the solution correct?

User Jose Sosa
by
7.5k points

1 Answer

3 votes

Final answer:

The solution provided is not correct.

Step-by-step explanation:

The solution provided, (x²+10x+9)/(x+9)=(x²+10x)/(x)=x+10, is not correct.

To solve this equation, we need to simplify the left side using the concept of factoring. We first factor the numerator of the left side of the equation to (x+9)(x+1). We can cancel out the common factor of (x+1) in both the numerator and denominator, resulting in (x+9)/(x)=(x²+10x)/(x²)=x+9.

Therefore, the correct solution is (x+9)/(x)=x+9.

User Noamik
by
7.3k points